2021
DOI: 10.1136/ijgc-2021-002888
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of advanced epithelial ovarian cancer after neoadjuvant chemotherapy: a phase II prospective multicenter non-randomized trial (the CILOVE study)

Abstract: ObjectiveThe aim of this study was to explore the feasibility and safety of the laparoscopic approach after neoadjuvant chemotherapy among selected chemosensitive patients with advanced ovarian cancer.MethodsThe CILOVE study was a phase II prospective non-randomized multicenter study. It aimed to enroll 47 women with unresectable disease at the time of initial diagnosis (International Federation of Gynecology and Obstetrics (FIGO) stage IV and/or diffuse extensive carcinomatosis for advanced FIGO stage IIIC or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Lately the use of laparoscopy was extended to patients with advanced disease to help identify women with disease amenable to complete resection [ 31 32 ]. As previously mentioned, 2 recent studies, the CILOVE and MISSION trials [ 23 24 ], were published. From the latter a subsequent international multi-centric trial stemmed [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately the use of laparoscopy was extended to patients with advanced disease to help identify women with disease amenable to complete resection [ 31 32 ]. As previously mentioned, 2 recent studies, the CILOVE and MISSION trials [ 23 24 ], were published. From the latter a subsequent international multi-centric trial stemmed [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, the ultimate attempt has been, in recent years, the use of laparoscopy to complete the whole surgical debulking [ 21 22 ]. Two trials have been published on the laparoscopic treatment of OC: the MISSION and CILOVE trials [ 23 24 ]. Both trials focused on patients who underwent neoadjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…A residual tumor of 0 and 0.5 cm was achieved in 29 (96.6%) patients and 1 (3.4%) patient, respectively [ 59 ]. The CILOVE study reported that all except one patient had optimal cytoreduction (97% complete cytoreduction, 3% incomplete cytoreduction) [ 60 ]. Both trials indicated that the role of laparoscopy has become more crucial in the management of ovarian cancer.…”
Section: Laparoscopic Surgery As An Alternative To Laparotomymentioning
confidence: 99%
“…In the advanced EOC study, only selected patients had similar disease‐free and overall survival rates between the two groups; moreover, patients with widespread disease were mostly excluded from the laparoscopy group. The clinical effect of laparoscopic surgery strongly depends on the proficiency of the surgeon 31–37 . However, there is insufficient high‐quality evidence that supports laparoscopy as a substitute for laparotomy in managing EOC, regardless of the stage.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical effect of laparoscopic surgery strongly depends on the proficiency of the surgeon. 31 , 32 , 33 , 34 , 35 , 36 , 37 However, there is insufficient high‐quality evidence that supports laparoscopy as a substitute for laparotomy in managing EOC, regardless of the stage. Currently, laparotomy is the routine treatment for EOC.…”
Section: Introductionmentioning
confidence: 99%